Pengembangan Bahan Ajar Hewan Mamalia Indonesia Berbasis Ensiklopedia Untuk Siswa Kelas IV Sekolah Dasar - Nadra, Wawan Suprianto; Jabu, Sartika A.; Pamuti, Pamuti (EDUKASI, 2024)
This research aims to determine the validity and practicality of Indonesian mammal teaching materials based on encyclopaedia for Year IV elementary school students. It is a research and development (RD) study employing the ADDIE model, though it is limited to the development phase. The subjects of research include content experts, language experts, and learning experts. Data collection techniques used in this study are interviews and questionnaires. This research resulted in a product consisting of educational materials about Indonesian mammals based on an encyclopedia. Based on validation conducted by expert lecturers in the subject matter, language experts, and teachers as learning experts, the scores received were 93.33% from the subject matter expert, 80% from the language expert, and 94.66% for the practicality of the educational materials by teachers. The educational materials about Indonesian mammals based on an encyclopedia can be categorised as highly valid and very practical, indicating that the product is suitable for trial testing with students.